Saudi Folktales and the Cultural Imagination in the Narratives of Abdo Khal (A Semiotic Approach to the Hijazi Tale of "Omar the Orphan") - Al-Ghamdi, Amjad Muidh; Al-Fawaz, AlReem Mufawaz (Arab Journal for Sciences and Research Publishing, 2025)
Saudi folk tales contain a semantic richness that reflects the richness of the Saudi human spirit, the son of the Arabian Peninsula, and the breadth of his imagination and its connection to him and his place. The study deals with one of the tales recorded by Abdo Khal in (Hamida Said: Hijazi Legends), in which the effects of Arab culture appear through its symbols and its influence by the geographical environment with its places and creatures, as in (the palm tree) and (the moon), which played a pivotal role in the tale. The study then reveals the cultural imagination and its connotations by addressing the structure of the content. The study approaches the story with the semiotics of narration and the semiotics of culture to conclude with the overlap of the path of the selves in the “factor structure” and the monitoring of the opposing dualities in the “semiotic universe” to reveal the memory of the text belonging to the field of (existence/non-existence).
Keywords: Hamida said; Hijazi myths; narrative semiotics; semiotics; the semiotic universe; the cultural imagination; folk literature; the Saudi story